Electron Spin Resonance and Thermoluminescence dating of shells and sediments from Sambaqui (shell mound) Santa Marta II, Brazil - LM Oliveira; MB Gomes; B Cortez; MC D'Oca; L Tranchina; E Tomarchio; A Parlato; JFD Chubaci; R Gennari; RR Rocca6; F d'Errico; S Sousa; et al. (Annals of Marine Science - Peertechz Publications, 2020)
In Tupi, the word Sambaqui means "mound of shells". These archaeological sites are cultural vestiges left by the prehistoric occupation of the Brazilian coast from five to six thousand years ago. Mollusks, fishes, and other marine edible foods were important for the survival of this population. The remains of foods, mainly shells, were heaped up, giving a mound of different proportions, which became part of the landscape of the Brazilian coastal plain. Due to the large number of Sambaquis in Brazil and considering that Sambaqui Santa Marta II, Laguna, SC, has not yet been dated, Electron Spin Resonance (ESR) measurements were performed in aragonite shells collected from different layers of Sambaqui Santa Marta II, starting from the base to the center of the Sambaqui. Radiocarbon analysis by Accelerator Mass Spectrometry (AMS) at Beta Analytic laboratory were also performed for comparison with ESR results. Before measurements, shells were chemically etched, after drying, were pulverized and sieved. The sediments were separated into small portions which were irradiated with gamma radiation from a 60Co source with doses from 5 up to 120 Gy. Ages around 2,000 to 4,000 years have been obtained. The results obtained are consistent with the dates of others Sambaquis of the region, possibly were built at the same time.